2009
DOI: 10.1148/radiol.2531082092
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of 174 Middle Cerebral Artery Aneurysms: Clinical Outcome and Radiologic Results at Long-term Follow-up

Abstract: EVT of MCA aneurysms was safe and long-term monitoring of patients showed a low rate of recurrence requiring retreatment. However, complex anatomy and long-term recurrences have to be addressed when considering EVT for MCA aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
3
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 23 publications
4
44
3
8
Order By: Relevance
“…Of note, we used the number of patients involved as our denominator to figure out morbidity-mortality. The morbidity and mortality rates in our series are similar to those in previous EVT studies in selected cases such as the results by Suzuki et al 8 and Vendrell et al 9 Meanwhile, morbidity-mortality of surgical clipping of MCA aneurysms is largely variable, ranging from 1.8 -13.6%. [3][4][5]15 Recently the UCSF neurosurgical group reported a 5.3% mortality rate and a 4.6% permanent morbidity rate after managing 631 MCA aneurysms (51.9% ruptured aneurysms) in 543 patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Of note, we used the number of patients involved as our denominator to figure out morbidity-mortality. The morbidity and mortality rates in our series are similar to those in previous EVT studies in selected cases such as the results by Suzuki et al 8 and Vendrell et al 9 Meanwhile, morbidity-mortality of surgical clipping of MCA aneurysms is largely variable, ranging from 1.8 -13.6%. [3][4][5]15 Recently the UCSF neurosurgical group reported a 5.3% mortality rate and a 4.6% permanent morbidity rate after managing 631 MCA aneurysms (51.9% ruptured aneurysms) in 543 patients.…”
Section: Discussionsupporting
confidence: 89%
“…6 However, most of these series were highly focused on selected patients. [7][8][9][10] To date, with the advent of new endovascular tools such as balloons and stents designed specifically for the intracranial circulation, MCA aneurysms can be managed by means of the endovascular approach. However, the safety and efficacy of EVT for all patients are not well known yet.…”
mentioning
confidence: 99%
“…21 In a series consisting of 174 MCA aneurysms, a 27.2% recanalization rate was reported of the 114 aneurysms that had follow-up with angiography. 22 From this perspective, the 2.2% recanalization rate that was achieved with DSAC seems promising. Throughout the time of this study, a wide variety of other methods have been defined for stent application in bifurcation aneurysm treatment such as linear stent placement, 23 nonoverlapping Y-stent placement, 24 the waffle-cone technique, 25 and so forth, which are mostly limited to anecdotal case series or a single case report.…”
mentioning
confidence: 96%
“…In other endovascular series of at least 50 patients, re-treatment rates varied from 2.4%-13.9%. [10][11][12][13][14]32 It is well recognized that the decision to re-treat is highly variable. 37 Our cohort had no additional morbidity or mortality relating to the additional procedures, and in line with previous findings, 38,39 the risk for further coil embolization did not negate the advantage of the initial embolization.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…The perforation rate lies within the range of previously published studies that have demonstrated procedural perforation complicating 1%-8.5% of MCA aneurysm treatments. [10][11][12][13][14]32 In 2 large prospective series of unruptured aneurysms (ATENA) 45 and ruptured aneurysms (CLARITY) treated by endovascular means, the perforation rate for MCA aneurysms was 4.1% and 8.5%, respectively. We have previously suggested that the rate of aneurysmal perforation may be higher at the MCA location 15 ; we demonstrated that MCA aneurysms accounted for 13% of cases but 24% of all intraprocedural ruptures.…”
Section: Morbidity and Mortality Outcomesmentioning
confidence: 99%